Impacts of Agroforestry Systems on Soil and Nutrient Conservation in the Eastern Himalayas, India - Bhatt, B. P.; Parmar, Brajendra; Bordoloi, L. J.; Benjamin; Bhattacharyya, Ranjan (International Journal of Bio-resource and Stress Management, 2016)
In a field experiment, soil moisture, soil and nutrient losses, and surface run-off in agri-silviculture (hedgerow and alder based) and agri-horticulture (guava based) agroforestry systems (AFS) were monitored for five consecutive years (2002–2006). Soil moisture was significantly (p=0.05) higher in agri-silvi based AFS compared with sole crop field (control; without a tree). On average, soil loss was 1.97±0.19, 8.91±0.98 and 12.49±1.22 t ha-1, respectively, in hedgerow, alder and guava based AFS compared to as high as 35.27±2.96 t ha-1 in the control plots. Mean (of all AFS systems) surface run-off was about 70% less in the plots under AFS compared with the control plots (1643.4 mm). Hedgerow based AFS was most efficient in minimizing surface run-off compared to other land use systems. Rainfall had significant positive (p<0.01) correlation with soil and nutrient loss. Significant monthly variations were also observed for nutrient loss in different AFS. Irrespective of monthly variations, organic carbon loss ranged from 1.09±0.04–1.11±0.10% in different AFS compared to 0.96±0.06% in control. Average nitrogen loss ranged from 172.0±11.45–175.08±9.43 kg ha-1 in various AFS as against of 169.17±12.33 kg ha-1 in control plots. Range of phosphorus and potassium loss was, respectively, 6.19±0.63–6.49±0.54 and 165.0±11.45–175.08±13.05 kg ha-1. In control plots, loss of phosphorus and potassium was found to be 6.49±0.33 and 169.0±10.50 kg ha-1, accordingly. All these systems have been reported to be ecologically and economically viable in the region.